Keberadaan Badan Akreditasi Provinsi Sekolah/Madrasah (Upaya Meningkatkan Mutu Pendidikan Madrasah Di Provinsi Jambi) - Jailani, M. Syahran (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
This research is intended to look into the existence of Province Acreditation for School and Islamic School in Jambi through the policies and programs executed, include the result of acreditation for islamic school at Ministry of Religious Affairs in Jambi. The data from Jambi Ministry of Religious Affairs in 2012 showed that from 538 islamic schools which have been acreditated, ie:(a) 244 Islamic Kindergarten, 169 (7,63%) kindergartens were acreditated, 75 (28,37%) kindergartens were not acreditated, (b). 263 Islamic Elementary School, 171 (61%) schools were acreditated, 98 (38,20%) schools were not acreditated, (c) 345 Islamic Junior High School, 158 (44,99 %) schools were acreditated, 187 (55,01%) schools were not acreditated and (d) 184 Islamic Senior High School, 88 (47,01%) schoolswere acreditated and 96 (52,99%) schools were not acreditated. From 1036 educational institutions, there have been 450 (43,44%) islamic schools which were acreditated while there were 586 (56,56%) isclamic schools which were not acreditated. The main problem which happenned was there were many islamic schools got C in acreditation and even some schools were not acreditated. It was caused by: (a) socialization, (b) limitted fund, (c) geographical condition, (d) the low network among islamic schools and (e) there were many policies which have not been accompanied by commitment fully.Keywords : Madrasah/School Acreditation Board, The Quality Of Madrasah Education.